(untitled) (Jurnal Bahasa, 2023)
In the Malaysian context, there are very few studies related to interaction structure in media conferences. In general, a media conference is a platform to convey information to the society. The question that the researcher aims to answer in this study is whether a Malaysian media conference is structured or not. As such, there are two objectives in this study, namely to identify the interaction structure and to discuss the arrangement of the interaction structure found in the Ministry of Health Malaysia’s COVID-19 media conference. This study uses a qualitative method by downloading a YouTube recording and analyzing the text content. The research material is a recording of the COVID-19 media conference on May 8, 2021, that was transcribed into written form, which is done by applying the transcription symbols by Jefferson (2004). Each utterance found in this transcription was analyzed using the framework of Theory of Conversation Analysis by Liddicoat (2011) and the Interaction Structure Model by Asmah (2010). The findings of the study show that there are nine aspects of the interaction structure in this media conference, namely sequence opener, introduction of speaker, purpose statement, question and answer, turn taking, overlapping, adjacent pairs, correction and closing the conversation. This also shows that the speaker’s adherence to the interaction structure facilitates the question-and-answer session, hence making the information presented to be clearer and more accurate. Through this study, it can be proven that Malaysian media conferences that involve the Malaysian Ministry of Health is a media conference with its own distinctive structure. Keywords: Interaction structure, Liddicoat’s Theory of Conversation Analysis (2011), Asmah’s Interaction Structure Model (2010), media conference, COVID-19, transcription Full text: PDF